Bibliography on Land-Locked States, Economic Development and International Law - Glassner, Martin Ira (M.E. Sharpe, 2001)
Keywords: Bibliography; Bibliography; Access to the sea (International law); Landlocked states; dept.egm; faculty_collection

The lead project. An environmental instrumental analysis case study - Breslin, V.T.; Sañudo-Wilhelmy, S.A. (Journal of Chemical Education, 2001)
19 citations (Crossref) [2023-10-31]
Keywords: dept.egm; peer-reviewed

Modem japanese geography: an intellectual history. - Martin, GJ (Professional Geographer, 2001)
tex.unique-id: ISI:000172890700020
Keywords: dept.egm; ⛔ No DOI found

Influence of soil moisture on the sequestration of organic compounds in soil. - Kottler, Bennett D.; White, Jason C.; Kelsey, Jason W. (Chemosphere, 2001)
A study was conducted as a part of continuing investigation of the effect of soil moisture on the sequestration of organic compounds aged in the soil. Here, experiments focused on the effects of moisture changes within the soil before, during, and after contaminant addition. The extractability of aged (68 d) phenanthrene was greater from soil that had been subjected to wetting and drying cycles prior to solute addition as compared to soil initially maintained at constant moisture. The recovery of phenanthrene added to moist soil was increased relative to extractability from soil that was air-dried at the time of the contaminant addition. Repeated wetting and drying of soil after the addition of atrazine or phenanthrene resulted in decreased extractability of the compounds as compared to samples maintained at constant moisture. A method for rapidly sequestering contaminants is proposed and may be useful in limiting the time required for laboratory studies involving "aged" contaminants. These data build upon the findings of earlier work from our laboratory and indicate that changes in the moisture conditions of soil can affect the availability of sequestered contaminants possibly through alterations in the structure of the natural solid. © 2001 Elsevier Science Ltd.
46 citations (Crossref) [2023-10-31] Citation Key Alias: pop00068 tex.type: [object Object]
Keywords: Aging; Atrazine; Bioavailability; Biological Availability; Extraction; Organic Chemicals; Phenanthrene; Phenanthrenes; Soil; Soil Pollutants; Water; article; atrazine; bioavailability; chemical structure; dept.egm; extraction; leaching; moisture; organic compound; phenanthrene; phenanthrene derivative; soil moisture; soil pollution; solid state; wetting-drying cycle